Boj znotraj boja - Alič, Špela (Etnolog. Nova vrsta (Ljubljana), 2012)
To understand the struggle of women Zapatistas it is important to know about the struggle of the Zapatistas itself, which is described in detail in the first part of the article. The second part describes the double struggle womenhave been fighting since the 1994 uprising, a struggle at both the national and local levels to be recognised as women, indigenous inhabitants, and equal members of society.
Keywords: Mehika; Mexico; zapatizem; neoliberalizem; ženske; woman; politics; politika